Growth and optical properties of dye films and dye-in-polymer matrix deposited by vacuum evaporation - Grytsenko, K.; Doroshenko, T.; Kolomzarov, Yu.; Lytvyn, O.; Serik, M.; Tolmachev, O.; Slominski, Yu.; Schrader, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Searching new more effective materials for organic electroluminescent
displays is continuing. The polymethine dyes is a class of organic materials that are very
interesting for these purposes. Films of the polymethine dyes were deposited by
evaporation in vacuum. Also deposited were dye-filled polytetrafluoroethylene (PTFE)
films. Kinetics of growth and heating the films were observed using optical spectroscopy
in situ. It was found out the influence of the chemical structure of dyes on growth and
heating kinetics of the dye films. It was found that PTFE matrix strongly enhances dye
stability.